Semut sebagai vektor mekanik bakteri di dalam gedung Balai Litbang P2B2 Tanah Bumbu, Kalimantan Selatan: studi pendahuluan - Ika Setianingsih; Muhammad Rasyid Ridha; Syarif Hidayat; Dicky Andiarsa (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2017)
Ants are now now noticeable as a mechanical vector of pathogenic bacteria, some of which have been resistant to certain antibiotics. Its wide presence allows ants to easily transmit disease agents. This study aims to determine the type of ants in Balai Litbang P2B2 Tanah Bumbu and possible role as a vector mechanical bacteria. This research was conducted at Balai Litbang P2B2 Tanah Bumbu from August to September 2017, the sample was obtained from 15 rooms by using the sugar solution feed placed in the microtube, then the ant was identified by referring to Key to Identifying Common Household Ants and Pictorial Key to the Common Urban Ants of North Carolina, followed by identification of bacteria on selective and biochemical media referring to Bergey's Manual of Systematic Bacteriology Volume 2. Out of a total of 16 samples, five types of ants are known: Tapinoma melanochephalum, Paratrechina longicornis, Tetramorium caespitum, and Anoplolepis gracilipes , and Solenopsis spp. Bacteria are found in all types of ants. The bacteria identified were Bacillus alvei, Bacillus badius, Bacillus insulitus, Serratia liquefaciens, Enterobacter aglomerans, and Klebsiella ozonae, and Enterobacter spp. The ants found in Balai P2B2 Tanah Bumbu are potentially bacterial mechanical vectors.